Endoscopic Management for Patients with Serrated Polyposis Syndrome is Feasible and Effective: - Knabe, M.; Behrens, A.; Ell, C.; Tannapfel, A.; Pohl, J. (Zeitschrift für Gastroenterologie, 2014)
Background and Study Aims: Serrated polyposis syndrome is a rare condition in which multiple serrated lesions develop all over the colon, which is thought to be associated with an increased risk for the development of cancer. The aim of this study was to investigate the feasibility of endoscopic treatment and standardised surveillance in patients with this increasingly recognised syndrome.Methods: From September 2010 to November 2013, consecutive patients were included in a prospective study. All patients underwent chromoendoscopy at first presentation and during surveillance. Follow-up examinations were carried out at 3 month intervals until complete clearance was achieved. Afterwards, patients entered a standardised surveillance protocol with a chromoendoscopic colonoscopy annually.Results: Altogether 100 colonoscopies were carried out in 28 patients, with endoscopic resection of 436 lesions. Total clearance was accomplished in 27 patients (96.0 %) after 2.5 colonoscopies (range 1 – 8). Histology revealed 359 hyperplastic polyps (82.3 %), 37 sessile serrated adenomas (8.5 %), 36 low-grade adenomas (8.3 %), and one patient with advanced colorectal cancer. Twelve patients (42.8 %) had serrated polyps > 10 mm in size. During the surveillance period, 86 additional lesions were detected and resected. The mean follow-up period was 21.5 months (range 2 – 39 months). No interval carcinoma was detected during the surveillance.Conclusions: The present study indicates that endoscopic management in patients who meet the diagnostic criteria for serrated polyposis syndrome is feasible and safe. In particular, the incidence of colorectal cancer in this cohort was lower in comparison with previous studies.
Keywords: kolorektales Karzinom; kolorektales Adenom; intraepitheliale Neoplasie